Effects of viscoelastic properties of tendon structures on stretch-shortening cycle exercise in vivo - Kubo, K.; Kanehisa, H.; Fukunaga, T. (Journal of Sports Sciences, 2005)
The aim of the present study was to examine the effects of viscoelastic properties of human tendon structures during stretch-shortening cycle exercise. The elongation of tendon and aponeurosis of the medial gastrocnemius muscle of 26 participants was measured by ultrasonography while they performed ramp isometric plantar flexion up to the voluntary maximum, followed by a ramp relaxation. The relationship between estimated muscle force and tendon elongation during the ascending phase was fitted to a linear regression, the slope of which was defined as stiffness. The percentage of the area within the muscle force-tendon elongation loop relative to the area beneath the curve during the ascending phase was defined as hysteresis. In addition, maximal voluntary concentric contractions at 2.09 and 3.14 rad·s-1 with and without prior eccentric contractions were performed. The difference in the concentric torque at equivalent joint angles with and without prior eccentric contractions (i.e. pre-stretch augmentation) was negatively correlated with stiffness (P<0.05) and hysteresis (P<0.05). Furthermore, there was a higher correlation between the pre-stretch augmentation and the viscoelastic properties index - that is, the sum of normalized score values of stiffness and hysteresis (P<0.01) - than with either stiffness or hysteresis alone. The results of this study suggest that performance during stretch-shortening cycle exercise is significantly affected by the viscoelastic properties of the tendon structures.